Ms Graffiti’s Spatial Contestation: An Observational Analysis on Church Street - Monika C, Arockia Licy (Street Art & Urban Creativity, 2024)
Graffiti in India – what does it mean? The graffiti scenario in India is something that is measuring grounds. However, what exactly is happening with the diverse forms of graffiti in India? Graffiti in the West and Europe are recognised as cultural movement of their own. Does such impactful street and public art create cultural impact in India? Though research indicates the trajectory of graffiti artists is to have their art up-ended into museum and gallery spaces from streets and public spaces, the movement began in public spaces. In India there are studio spaces and galleries for Graffiti however, the public and street art of the same is rarely seen in its authenticity. The essentiality of graffiti is being transformed from a rebellious and daring self-expression within a public space to a more institutionalized, tailored and commodified essentiality of private spaces. Can this enclosed art space aid or create something of cultural impact? This paper aims to analyse tags in church street in Bangalore, Karnataka to be creating a spatial contestation, through its different types of graffiti present within its spread of 750 meters. By using Lefebvre’s theory of The Production of Space, this article aims to understand the spatial relevance of Graffiti and tags in Church street, Bangalore, India. This spatial approach to understanding the graffiti and tags in church street helps in understanding the art practice better for spatial analysis exposes their essentiality.